Analysis of the Growth Rate of Goods and Services Tax Revenue for Hospitality Services and its Contribution to Local Revenue in the Province of Jakarta Special Region - Hidayat, Rehan; Setyowati, Milla Sepliana (Electronic Journal of Education, Social Economics and Technology, 2025)
Jakarta, as the economic and tourism centre of Indonesia, has a strong attraction for tourists, as well as businesspeople from various directions. Hotel Services Revenue has an impact on PBJT Hotel Services Revenue, which is one source of local tax revenue. This study aims to analyse the growth rate of the Specific Goods and Services Tax (PBJT) from the hotel services sector and its contribution to Local Government Revenue in the Special Region of Jakarta Province during the period 2019-2024. This research uses a descriptive analysis method with a quantitative approach. Secondary data includes the realisation of PBJT revenue from the hotel services sector and the total Local Government Revenue of the Special Region of Jakarta. The results of this study indicate that the growth rate of PBJT revenue from the hotel services sector in Jakarta tends to increase annually, as does the contribution of PBJT Hospitality Services, which also continues to rise every year. However, the contribution falls into the "very low" category.